PENINGKATAN PEMAHAMAN DAN KETERAMPILAN MAHASISWA TERHADAP PENGGUNAAN BAHASA INDONESIA DAN BAHASA DAERAH DALAM PEMBELAJARAN DARING - Hiariej, Chrissanty; Patty, Jusak (Universitas Mataram, 2024)
The appropriate use of Indonesian and local languages in online learning has become a significant concern in academic settings. Using Indonesian can facilitate effective communication between educators and learners from diverse cultural and local language backgrounds. Meanwhile, using local languages can help learners understand the material better, especially for those more familiar with the language. This training aims to enhance the understanding and skills of students in the Indonesian Language and Literature Education Program at the Faculty of Language and Literature Education, Pattimura University, in using both languages effectively and contextually. The online training session was conducted on 8 December 2023, involving 47 participants. The training materials covered understanding the functions and positions of Indonesian and local languages, ethics and norms in language usage in online learning, and effective communication strategies and practices using both languages. Teaching methods included lectures, discussions, case studies, and practical exercises facilitated by competent language experts. Evaluation was carried out through questionnaires, observations, and participant feedback. The evaluation results indicated that the training session achieved its targeted success indicator, with a minimum of 80% of participants experiencing improved understanding and proficiency in using both languages appropriately. Participants felt that this training increased their confidence in Indonesian and local languages. In addition, participants felt more confident in using both languages in various online learning situations, and their communication skills in both languages improved. It is concluded that continuous training involving competent facilitators and regular updates of training materials are necessary to ensure sustained improvement in language skills within academic environments.